The use of treated wastewater in Barbus xanthopterus and Ctenopharyngdon idella larvae culture - Alkatrani, Layla Mustafa A.A.; Yesser, Abdulkareem Taher (Iraqi Journal of Aquaculture, 2021)
Larvae of Luciobarbus xanthopterus and Ctenopharyngdon idella were cultured in ponds with treated wastewater in marine science center by adding 20 larvae to each pond in a replicate to each species as well as the control ponds to the two species. Experiment was expend to six weeks depending on the natural food available in the pond. While standard artificial diet was add to the control ponds. Some biological measurements were done including length and weight rates, weight increase and daily weight increase, relative and specific growth rates and survival rates. Results showed a clear excellence of treated wastewater ponds in all biological measurements from the control ponds at the tow species. Larvae of L. xanthopterus showed a length and weight rates, weight increase and daily weight increase and survival rates higher than C. Idella which were (4.41 ± 0.04) cm, (0.35 ± 0.06) gm, (0.322 ± 0.005) gm, (0.008 ± 0.0002) gm/day and (91.67 ± 2.89) % respectively, while C. Idella showed relative and specific growth rates higher than L. xanthopterus larvae which were (3790.40 ± 877.88) % and (8.85 ± 0.56) %gm/day respectively. The study showed that the use of treated wastewater in L. xanthopterus and C. Idella larvae culture was excellent and rise the growth and survival rates of these larvae.